Artificial graphite, preparation method thereof, negative electrode and lithium ion battery
By adding fluorinated coke ultrafine powder to the production of artificial graphite for lithium-ion batteries, the problem of the difficulty in utilizing ultrafine powder has been solved, resource utilization and battery performance have been improved, and production costs have been reduced.
Patent Information
- Application Number
- CN202511137479.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-21
AI Technical Summary
In the production process of artificial graphite anode materials for lithium-ion batteries, ultrafine powder is difficult to utilize, leading to resource waste and increased production costs.
Artificial graphite was prepared by mixing and granulating raw coke powder with modified solid-phase binder and liquid-phase binder, and adding fluorinated coke ultrafine powder to enhance the graphitization degree and electrical conductivity of the solid-phase binder after graphitization, thereby preventing the self-aggregation of coke ultrafine powder.
This enables full utilization of coke ultrafine powder, reduces production costs, and improves the recycling and rate performance of artificial graphite.
Smart Images

Figure CN120987313A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of battery materials, in particular to artificial graphite, a preparation method thereof, a negative electrode and a lithium ion battery. BACKGROUND
[0002] As the most widely used secondary battery at present, a lithium ion battery is usually composed of a positive electrode, a negative electrode, a separator, an electrolyte and a shell, etc. In the charging and discharging cycle process, the mutual conversion between electric energy and chemical energy is realized by relying on the embedding and de-embedding of lithium ions between the positive electrode and the negative electrode in the internal circuit, and the directional migration of electrons in the external circuit. Among them, the negative electrode plays a key role in storing and releasing lithium ions and conducting current in the battery system, and has a significant impact on the energy density, cycle performance, charging and discharging rate and low-temperature discharge performance of the battery. Among the many materials that can be used for the negative electrode, graphite has become the mainstream negative electrode material for large-scale commercial application due to its low cost, high structural stability, non-toxicity, good electrical conductivity and excellent mechanical properties.
[0003] In the production process of the artificial graphite negative electrode material of the lithium ion battery, the raw material coke (such as petroleum coke, needle coke, etc.) needs to be processed by crushing, pulverizing and other processes to a specific particle size (usually 5-20 μm) to meet the requirements of the subsequent granulation, graphitization and other processes for the particle size of the material. However, a certain amount of ultra-fine powder (particle size <2 μm) will inevitably be produced in the pulverizing process, which usually accounts for 5%-15% of the total mass of the raw material coke. This kind of ultra-fine powder is difficult to effectively utilize in the production process due to its extremely small particle size, resulting in waste of resources and increasing production costs. SUMMARY
[0004] Based on this, the present application provides an artificial graphite, a preparation method thereof, a negative electrode and a lithium ion battery.
[0005] In a first aspect, the present application provides a preparation method of artificial graphite, comprising:
[0006] The raw material coke powder and the modified solid phase binder and the liquid phase binder are sequentially subjected to first kneading and second kneading, granulation, to obtain a granulation precursor; wherein the modified solid phase binder comprises a mixture of a solid phase binder and a fluorinated coke ultra-fine powder;
[0007] The granulation precursor is graphitized to obtain the artificial graphite.
[0008] In some embodiments, the solid phase binder comprises one or more of coal tar pitch, petroleum pitch, phenolic resin, epoxy resin, polyacrylonitrile; and / or,
[0009] The softening point of the solid phase binder is above 150°C; and / or,
[0010] The liquid phase binder comprises one or more of emulsified asphalt, liquid phase asphalt, tar, and polyacrylic acid.
[0011] In some embodiments, the liquid phase binder further comprises a biomass-based binder, the biomass-based binder comprising one or more of lignin, cellulose, protein, amino acid, and starch; and / or,
[0012] The biomass-based binder in the liquid phase binder accounts for 20wt% to 45wt% of the mass.
[0013] In some embodiments, the mass ratio of the raw coke powder to the modified solid phase binder is 100:(2-5); and / or,
[0014] In the modified solid phase binder, the mass ratio of the solid phase binder to the fluorinated coke ultrafine powder is 100:(15-25); and / or,
[0015] The mass ratio of the raw coke powder to the liquid phase binder is 100:(6-8).
[0016] In some embodiments, the method for preparing the fluorinated coke ultrafine powder comprises:
[0017] The coke ultrafine powder is placed in a fluorine-containing atmosphere for fluorination treatment; the fluorine-containing atmosphere comprises a fluorine-containing gas, and the fluorine-containing gas comprises one or more of fluorine gas, nitrogen trifluoride, sulfur hexafluoride, carbon tetrafluoride, and hydrogen fluoride.
[0018] In some embodiments, the fluorination treatment comprises first fluorination treatment and second fluorination treatment performed sequentially;
[0019] The first fluorination treatment comprises: placing the coke ultrafine powder in a first fluorine-containing atmosphere, heating to 230°C to 270°C, and maintaining for 1 hour to 2 hours; the first fluorine-containing atmosphere comprises a fluorine-containing gas and a protective gas, and the volume ratio of the fluorine-containing gas in the first fluorine-containing atmosphere is 10% to 15%;
[0020] The second fluorination treatment comprises: placing the coke ultrafine powder subjected to the first fluorination treatment in a second fluorine-containing atmosphere, heating from 230°C to 270°C to 330°C to 370°C, and maintaining for 2 hours to 5 hours; the second fluorine-containing atmosphere comprises a fluorine-containing gas and a protective gas, and the volume ratio of the fluorine-containing gas in the second fluorine-containing atmosphere is 85% to 90%.
[0021] In some embodiments, before the fluorination treatment, the coke ultrafine powder is further subjected to nanocrystallization treatment; and / or,
[0022] The liquid phase dispersant is further added in the first kneading process; a mass ratio of the liquid phase dispersant to the raw material coke powder is (1-1.5):100; the liquid phase dispersant comprises one or more of sodium carboxymethyl cellulose, sodium dodecyl benzene sulfonate, sodium dodecyl sulfate, fatty acid soap, sodium polyacrylate, polycarboxylate, hydroxyethyl cellulose, and polyacrylate; and / or,
[0023] The graphitization temperature is 2800-3000 DEG C, and the graphitization duration is 70-85 hours; and / or,
[0024] The granulation comprises: heating the material obtained after the kneading to 250-290 DEG C, and maintaining the temperature for 4-6 hours; and then heating to 630-670 DEG C, and maintaining the temperature for 8-10 hours.
[0025] In a second aspect, the embodiments of the present application provide a synthetic graphite, wherein the synthetic graphite satisfies 0.89
[0026] In a third aspect, the embodiments of the present application provide a negative electrode comprising the synthetic graphite as described above.
[0027] In a fourth aspect, the embodiments of the present application provide a lithium ion battery comprising the negative electrode as described above.
[0028] The preparation method of the synthetic graphite provided by the embodiments of the present application comprises: sequentially performing first kneading and second kneading on raw material coke powder and modified solid phase binder and liquid phase binder, and then performing granulation to obtain a granulation precursor; wherein the modified solid phase binder comprises a mixture of a solid phase binder and coke ultrafine powder subjected to fluorination treatment; and performing graphitization on the granulation precursor to obtain the synthetic graphite. By adding the coke ultrafine powder to the solid phase binder, the graphitization degree and the electrical conductivity of the carbon layer of the solid phase binder after graphitization can be enhanced; by performing fluorination treatment on the coke ultrafine powder, the problem of self-agglomeration of the coke ultrafine powder can be avoided or alleviated, and the bonding force between the coke ultrafine powder and the solid phase binder can be enhanced; the preparation method can not only make full use of the coke ultrafine powder, improve the resource utilization rate, and reduce the production cost, but also make the synthetic graphite have good cycle performance and rate performance. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced.
[0030] Figure 1 The flow chart of the preparation method of the synthetic graphite provided by the embodiments of the present application. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person skilled in the art without creative work fall within the scope of the present application.
[0032] In the present application, the association relationship of the associated objects described by "and / or" indicates that there can be three kinds of relationships, for example, A and / or B can represent the following three cases: A exists alone, A and B exist simultaneously, and B exists alone. Wherein A and B can be singular or plural.
[0033] In the present application, "at least one" means one or more, and "multiple" means two or more. "One or more", "at least one of the following" or the like means any combination of these items, including any combination of single item or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can represent a, b, c, a+b, a+c, b+c, or a+b+c, wherein a, b, and c can be single or multiple.
[0034] "Parts by weight" refers to a basic unit of measurement indicating the mass ratio relationship of multiple components. 1 part can represent any unit mass, such as 1 g, 1 Kg, or 2 g, 2 Kg, etc. If we say that the weight of component A is a parts, and the weight of component B is b parts, it means that the mass ratio of component A to component B is a:b. Or, it means that the mass of component A is aK, and the mass of component B is bK (K is any number, indicating a multiple factor). It should not be misunderstood that unlike the weight fraction, the sum of the weight fractions of all components is not limited to 100 parts.
[0035] Various embodiments of the present application can exist in the form of a range; it should be understood that the description in the form of a range is only for the convenience and brevity, and should not be understood as a hard limit on the scope of the present application; therefore, it should be considered that the described range has been specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5, and 6. In addition, whenever a numerical range is indicated in this document, it refers to any cited number (fraction or integer) within the indicated range.
[0036] Please refer to Figure 1 The embodiments of the present application provide a preparation method of artificial graphite, comprising:
[0037] S100, sequentially mixing raw coke powder with modified solid phase binder and liquid phase binder to perform first kneading and second kneading, and granulating to obtain granulated precursor; wherein the modified solid phase binder comprises a mixture of solid phase binder and fluorinated coke ultrafine powder.
[0038] It should be noted that by adding coke ultrafine powder to the solid phase binder, the graphitization degree and electrical conductivity of the carbon layer of the solid phase binder after graphitization can be enhanced; by fluorinating the coke ultrafine powder, the problem of self-agglomeration of the coke ultrafine powder can be avoided or alleviated, and the bonding force between the coke ultrafine powder and the solid phase binder can be enhanced.
[0039] Exemplarily, both the coke ultrafine powder and the raw coke powder are obtained by crushing raw coke, and the raw coke comprises one or more of needle coke, petroleum coke, and pitch coke.
[0040] Exemplarily, the particle size D50 of the raw coke powder is 6.5 μm-10.5 μm, for example, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, etc.
[0041] Exemplarily, the particle size D50 of the coke ultrafine powder is less than or equal to 2 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, etc.
[0042] Exemplarily, the solid phase binder comprises one or more of coal tar pitch, petroleum pitch, phenolic resin, epoxy resin, and polyacrylonitrile.
[0043] Exemplarily, the particle size D50 of the solid phase binder is 3 μm-5 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.
[0044] Exemplarily, the softening point of the solid phase binder is above 150℃.
[0045] It should be noted that when the softening point of the solid phase binder is below 150℃, the solid phase binder may prematurely soften or even liquefy during the granulation process, resulting in excessive loss or uneven distribution of the binder during the mixing stage, and failing to form an effective bonding network inside the granules, and also resulting in excessively large pore size of the carbon layer of the artificial graphite prepared and poor cycle performance; while the solid phase binder with a softening point above 150℃ can maintain a proper solid or semi-solid state at the initial temperature of the granulation, and only gradually play a bonding role under the action of subsequent higher temperature after the material is uniformly dispersed, and the pore size of the carbon layer of the artificial graphite prepared is relatively small and the cycle performance is good.
[0046] Exemplarily, the liquid phase binder comprises one or more of emulsified asphalt, liquid phase pitch, tar, and polyacrylic acid.
[0047] Exemplarily, the liquid phase binder further comprises a biomass-based binder, and the biomass-based binder comprises one or more of lignin, cellulose, protein, amino acid, and starch.
[0048] It should be noted that by adding the biomass binder in the liquid phase binder, the biomass binder can be introduced into the carbon layer of the prepared artificial graphite particles to enhance the structural stability of the artificial graphite particles.
[0049] Exemplarily, the mass fraction of the biomass-based binder in the liquid phase binder is 20wt%-45wt%, for example, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, etc.
[0050] Exemplarily, the mass ratio of the raw coke powder to the modified solid phase binder is 100:(2-5), for example, 100:2, 100:3, 100:4, 100:5, etc.
[0051] Exemplarily, in the modified solid phase binder, the mass ratio of the solid phase binder to the fluorinated coke ultrafine powder is 100:(15-25), for example, 100:15, 100:18, 100:20, 100:22, 100:25, etc.
[0052] Exemplarily, the mass ratio of the raw coke powder to the liquid phase binder is 100:(6-8), for example, 100:6, 100:7, 100:8, etc.
[0053] Exemplarily, the preparation method of the fluorinated coke ultrafine powder comprises:
[0054] The coke ultrafine powder is placed in a fluorine-containing atmosphere for fluorination treatment; the fluorine-containing atmosphere comprises a fluorine-containing gas, and the fluorine-containing gas comprises one or more of fluorine gas, nitrogen trifluoride, sulfur hexafluoride, carbon tetrafluoride, and hydrogen fluoride.
[0055] Exemplarily, the fluorination treatment comprises first fluorination treatment and second fluorination treatment performed in sequence.
[0056] The first fluorination treatment comprises: placing the coke ultrafine powder in a first fluorine-containing atmosphere, heating to 230°C-270°C, and holding for 1-2 hours; the first fluorine-containing atmosphere comprises a fluorine-containing gas and a protective gas, and the volume fraction of the fluorine-containing gas in the first fluorine-containing atmosphere is 10%-15%;
[0057] The second fluorination treatment comprises: placing the first fluorination treated coke ultra-fine powder in a second fluorine-containing atmosphere, and heating from 230-270 DEG C to 330-370 DEG C, and holding for 2-5 hours; the second fluorine-containing atmosphere comprises fluorine-containing gas and protective gas, and the volume ratio of the fluorine-containing gas in the second fluorine-containing atmosphere is 85-90%.
[0058] It should be noted that the first fluorination treatment is mainly for fluorination of the sharp edges on the surface of the coke ultra-fine powder, and the second fluorination treatment is mainly for fluorination of the flat parts on the surface of the coke ultra-fine powder.
[0059] Exemplarily, the protective gas comprises one or more of nitrogen and inert gas, and the inert gas comprises one or more of helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe).
[0060] Exemplarily, the heating rate during the first fluorination treatment is 5-10 DEG C / min, and the heating rate during the second fluorination treatment is 2-5 DEG C / min.
[0061] Exemplarily, before the fluorination treatment, the coke ultra-fine powder is further subjected to a nanocrystallization treatment.
[0062] It should be noted that the nanocrystallization treatment can reduce the particle size of the coke ultra-fine powder to the nanometer level, and make the particle size of the coke ultra-fine powder more uniform, thereby improving the uniformity of the mixture of the coke ultra-fine powder and the solid phase binder.
[0063] Exemplarily, the nanocrystallization treatment comprises: ball milling the coke ultra-fine powder, the ball-to-material ratio is (10-15):1, the ball milling speed is 600-800 r / min, and the ball milling time is 18-36 hours.
[0064] Exemplarily, after the nanocrystallization treatment, the particle size D50 of the coke ultra-fine powder is less than or equal to 500 nm, for example, 500 nm, 400 nm, 300 nm, 200 nm, 100 nm, 50 nm, 10 nm, etc.
[0065] Exemplarily, a liquid phase dispersant is further added during the first kneading; the mass ratio of the liquid phase dispersant to the raw material coke powder is (1-1.5):100; and the liquid phase dispersant comprises one or more of sodium carboxymethyl cellulose, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, fatty acid soap, sodium polyacrylate, polycarboxylate, hydroxyethyl cellulose, and polyacrylate.
[0066] Exemplarily, the mass ratio of the liquid-phase dispersant to the raw coke powder can be 1:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100.
[0067] It should be noted that by adding the liquid-phase dispersant, the mixing uniformity of the raw coke powder and the liquid-phase binder can be improved when the raw coke powder is mixed with the liquid-phase binder.
[0068] Exemplarily, the granulation comprises: heating the material obtained after mixing to 250-290°C, maintaining for 4-6 hours, and then heating to 630-670°C, maintaining for 8-10 hours.
[0069] Exemplarily, the material obtained after mixing is heated to 250-290°C at a heating rate of 3-6°C / min, and heated from 250-290°C to 630-670°C at a heating rate of 5-7°C / min.
[0070] S200, graphitizing the granulated precursor to obtain artificial graphite.
[0071] Exemplarily, the graphitization is performed in an Acheson furnace.
[0072] Exemplarily, the graphitization temperature is 2800-3000°C, for example, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, etc.
[0073] Exemplarily, the graphitization time is 70-85 hours, for example, 70 hours, 72 hours, 75 hours, 78 hours, 80 hours, 82 hours, 85 hours, etc.
[0074] Exemplarily, before graphitizing the granulated precursor, the granulated precursor is sent into a carbonization furnace for carbonization, the carbonization temperature is 1050-1250°C, and the carbonization time is 11-19 hours.
[0075] The application provides a preparation method of artificial graphite. The method comprises the following steps: sequentially mixing and kneading raw coke powder, modified solid-phase binder and liquid-phase binder to obtain a granulated precursor, wherein the modified solid-phase binder comprises a mixture of a solid-phase binder and coke ultrafine powder subjected to fluorination treatment; and graphitizing the granulated precursor to obtain artificial graphite. The coke ultrafine powder is added to the solid-phase binder to increase the graphitization degree and electrical conductivity of the carbon layer of the solid-phase binder after graphitization. The coke ultrafine powder is subjected to fluorination treatment to avoid or relieve the self-agglomeration of the coke ultrafine powder and to increase the bonding force between the coke ultrafine powder and the solid-phase binder. The preparation method can fully utilize the coke ultrafine powder, improve resource utilization and reduce production cost. Moreover, the artificial graphite prepared by the method has good cycle performance and rate performance.
[0076] The application provides artificial graphite prepared by the preparation method of artificial graphite.
[0077] The application provides a negative electrode comprising the artificial graphite.
[0078] The application provides a lithium ion battery comprising the negative electrode.
[0079] Exemplarily, the negative electrode comprises a negative electrode current collector, a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer and the second negative electrode active material layer are arranged on opposite sides of the negative electrode current collector, and at least one of the first negative electrode active material layer and the second negative electrode active material layer comprises the artificial graphite.
[0080] The application provides artificial graphite and a preparation method thereof.
[0081] Embodiment 1
[0082] A preparation method of artificial graphite comprises the following steps:
[0083] Step 10, provide raw coke (petroleum coke), dry and crush the raw coke to obtain raw coke powder (aggregate) with a particle size D50 of 8.5 μm and coke ultrafine powder with a particle size D50 of 1 μm; place the coke ultrafine powder in a fluorination reaction furnace, and pass a fluorine-containing atmosphere (fluorine gas and inert gas are blended) at a flow rate of 70 ml / min, two-stage fluorination, the first stage is pre-fluorination at room temperature to 250℃ (the volume fraction of inert gas in the fluorine-containing atmosphere is 88%), the heating rate is 7.5℃ / min, and the constant temperature is 1.5 hours; the second stage is fluorination at 300℃ (the volume fraction of fluorine gas in the fluorine-containing atmosphere is 88%), the heating rate is 3.5℃ / min, and the constant temperature is 3.5 hours, and the fluorinated coke ultrafine powder can be obtained after cooling.
[0084] Step 20, uniformly mix the fluorinated coke ultrafine powder and the solid phase binder (coal tar pitch) with a particle size D50 of 3.5 μm according to a mass ratio of 20:100 to obtain a modified solid phase binder, uniformly mix the modified solid phase binder and the aggregate (raw coke powder with a particle size D50 of 8.5 μm) according to a mass ratio of 3.5:100, add a liquid phase binder (emulsified asphalt) for solid-liquid kneading, the rotation speed is 35 Hz, the kneading time is 3.5 hours, and the mass ratio of the liquid phase binder to the aggregate (raw coke powder with a particle size D50 of 8.5 μm) is 7:100; then send into a reaction kettle, the temperature curve is two-stage, the first stage: heat from room temperature to 270℃ at a heating rate of 4℃ / min, keep at 270℃ for 3.5 hours, and the rotation speed is 18 Hz; the second stage: heat from 270℃ to 650℃ at a heating rate of 6℃ / min, keep at 650℃ for 9 hours, and the rotation speed is 25 Hz; then cool to room temperature; obtain the granulation precursor.
[0085] Step 30, send the granulation precursor into a carbonization furnace for carbonization, the carbonization temperature is 1150℃, the carbonization time is 15 hours, then perform graphitization in an Acheson graphitization furnace, the graphitization temperature is 2900℃, the power is supplied for 78 hours, then naturally cool and discharge, then perform mixing, two times of screening, and two times of magnetic removal to obtain artificial graphite.
[0086] Example 2
[0087] An artificial graphite, the difference between the preparation method and example 1 is that:
[0088] In step 20, the fluorinated coke ultrafine powder and the solid phase binder (coal tar pitch) with a particle size D50 of 3.5 μm are uniformly mixed according to a mass ratio of 15:100 to obtain a modified solid phase binder.
[0089] Example 3
[0090] An artificial graphite, the difference between the preparation method and example 1 is that:
[0091] In step 20, the modified solid phase binder is uniformly mixed with the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) at a mass ratio of 2:100.
[0092] Example 4
[0093] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0094] In step 20, the modified solid phase binder is uniformly mixed with the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) at a mass ratio of 5:100.
[0095] Example 5
[0096] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0097] In step 20, the modified solid phase binder is uniformly mixed with the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) at a mass ratio of 5:100.
[0098] Example 6
[0099] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0100] In step 20, the liquid phase binder is mixed with the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) at a mass ratio of 6:100.
[0101] Example 7
[0102] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0103] In step 20, the liquid phase binder is mixed with the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) at a mass ratio of 8:100.
[0104] Example 8
[0105] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0106] In step 10, the coke ultrafine powder is ball milled before being placed in the fluorination reaction furnace, the ball-to-material ratio is 13:1, the ball milling speed is 700 r / min, and the ball milling time is 27 hours, to obtain a nano-sized ultrafine powder.
[0107] Example 9
[0108] A synthetic graphite, the preparation method of which differs from that of Example 1 in that:
[0109] In step 20, before solid-liquid kneading with liquid binder (emulsified asphalt), solid-solid kneading is added with liquid dispersant (sodium carboxymethyl cellulose), the mass ratio of liquid dispersant to aggregate (raw material coke powder with particle size D50 of 8.5 μm) is 1.5:100, the rotation speed is 30 Hz, and the kneading time is 1 hour.
[0110] Example 10
[0111] A kind of artificial graphite, its preparation method compared with example 1, the difference is that:
[0112] In step 20, the liquid binder (emulsified asphalt) also includes biomass-based binder (lignin), and the mass fraction of biomass-based binder (lignin) in the liquid binder (emulsified asphalt) is 32.5wt%.
[0113] Example 11
[0114] A kind of artificial graphite, its preparation method compared with example 1, the difference is that:
[0115] In step 20, the liquid binder (emulsified asphalt) also includes biomass-based binder (lignin), and the mass fraction of biomass-based binder (lignin) in the liquid binder (emulsified asphalt) is 20wt%.
[0116] Example 12
[0117] A kind of artificial graphite, its preparation method compared with example 1, the difference is that:
[0118] In step 20, the liquid binder (emulsified asphalt) also includes biomass-based binder (lignin), and the mass fraction of biomass-based binder (lignin) in the liquid binder (emulsified asphalt) is 45wt%.
[0119] Example 13
[0120] A kind of artificial graphite, its preparation method compared with example 1, the difference is that:
[0121] In step 10, before placing the coke ultra-fine powder in the fluorination reaction furnace, the coke ultra-fine powder is ball milled, the ball-to-material ratio is 13:1, the ball milling rotation speed is 700r / min, and the ball milling time is 27 hours, to obtain nano-sized ultra-fine powder;
[0122] In step 20, before solid-liquid kneading with liquid binder (emulsified asphalt), a liquid dispersant (sodium carboxymethyl cellulose) is added for solid-solid kneading, the mass ratio of the liquid dispersant to the aggregate (raw material coke powder with a particle size D50 of 8.5 μm) is 1.5:100, the rotation speed is 30 Hz, and the kneading time is 1 hour; the liquid binder (emulsified asphalt) also includes a biomass-based binder (lignin), and the mass fraction of the biomass-based binder (lignin) in the liquid binder (emulsified asphalt) is 32.5 wt%.
[0123] Comparative Example 1
[0124] A method for preparing artificial graphite includes:
[0125] In step 11, raw coke (petroleum coke) is provided, dried, and crushed to obtain raw material coke powder with a particle size D50 of 8.5 μm.
[0126] In step 12, solid-phase binder (coal tar pitch) with a particle size D50 of 3.5 μm and raw material coke powder (aggregate) with a particle size D50 of 8.5 μm are uniformly mixed at a mass ratio of 3.5:100, and then put into a mechanical fusion machine for solid-solid kneading; then sent into a reaction kettle, the temperature curve is two-stage, the first stage: from room temperature to 270℃ at a heating rate of 4℃ / min, and kept at 270℃ for 3.5 hours, the rotation speed is 18 Hz; the second stage: from 270℃ to 650℃ at a heating rate of 6℃ / min, and kept at 650℃ for 9 hours, the rotation speed is 25 Hz; then cooled to room temperature; to obtain a granulation precursor.
[0127] In step 13, the granulation precursor is sent into a carbonization furnace for carbonization at a carbonization temperature of 1150℃ for 15 hours, and then into an Acheson graphitization furnace for graphitization at a graphitization temperature of 2900℃, and after 78 hours of power supply, the furnace is naturally cooled and discharged, then mixed, screened twice, and de-magnetized twice to obtain artificial graphite.
[0128] It can be seen that the difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not add coke ultra-fine powder when preparing artificial graphite, but only uses raw material coke powder (aggregate) with a particle size D50 of 8.5 μm and solid-phase binder (coal tar pitch) for blending.
[0129] Material property test:
[0130] The artificial graphite prepared in Examples 1-13 and Comparative Example 1 is tested for performance, and the test parameters and test methods are as follows:
[0131] Particle size: tested by Malvern Panalytical Zetasizer Ultra dynamic scattering particle size instrument;
[0132] Tap density: tested by using a CANTAB tap density instrument;
[0133] Specific surface area (BET): tested by using a CANTAB specific surface area tester;
[0134] Graphite orientation index (OI value): tested by using an X-ray diffraction instrument to obtain the ratio of 002 peak and 110 peak intensity;
[0135] Oil absorption value: tested by using a DABS-H oil absorption value tester;
[0136] Compacted density (5T): tested by using a Zwick universal testing machine;
[0137] Pore volume under no pressure and pore volume under 2T pressure: tested by using a F-Sorb 3400 multi-station pore size detector;
[0138] B: B = pore volume under 2T pressure / pore volume under no pressure.
[0139] The test results are shown in Table 1.
[0140] Table 1
[0141]
[0142]
[0143] As can be seen from Table 1:
[0144] The compacted density of the artificial graphite prepared in Examples 1-13 is higher than that of the artificial graphite prepared in Comparative Example 1, indicating that the artificial graphite prepared in Examples 1-13 has higher structural density; the artificial graphite prepared in Examples 1-13 can satisfy 0.89 < B < 1, while the B value of the artificial graphite prepared in Comparative Example 1 is less than 0.89, indicating that the artificial graphite prepared in Examples 1-13 has better structural stability.
[0145] Button cell test:
[0146] The preparation method of the button cell for testing electrochemical performance is as follows: the negative electrode material prepared in Examples 1-13 and Comparative Example 1 is mixed with conductive agent (SP), CMC, SBR according to a mass ratio of 95:1.5:1.5:2, and then coated on a copper foil, and the compacted density is 1.60 g / cm 3After vacuum drying, the electrolyte is used as the negative electrode, with lithium metal as the counter electrode. The electrolyte is a 1M LiPF6 mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a 1:1 mass ratio. The separator is a PE / PPPE composite membrane, forming a coin cell. Initial discharge capacity and efficiency were tested: Cyclic performance was tested at 3C current density with a charging voltage limited to 0.005-2V. Rate performance tests were also conducted at different rates (50 cycles at a single rate). The EIS internal resistance was measured using electrochemical impedance spectroscopy. The test results are shown in Table 2.
[0147] Table 2
[0148]
[0149] As can be seen from Table 2:
[0150] The artificial graphite prepared in Examples 1-13 exhibits higher initial discharge capacity, initial discharge efficiency, capacity retention after 1000 cycles at 1C at room temperature, and capacity retention at 4C rate than the artificial graphite prepared in Comparative Example 1. Furthermore, the artificial graphite prepared in Examples 1-13 has lower EIS internal resistance and 50-cycle expansion rate at 4C rate than the artificial graphite prepared in Comparative Example 1. This indicates that the cycling performance and rate performance of the artificial graphite prepared in Examples 1-13 are superior to those of Comparative Example 1. It is known that the preparation method of Comparative Example 1 is a traditional method for preparing artificial graphite, while the preparation method of this application involves fluorinating the coke ultrafine powder before adding it to the raw materials of artificial graphite. In other words, this application not only achieves efficient resource utilization of the coke ultrafine powder and reduces raw material costs, but also effectively improves the overall performance of artificial graphite.
[0151] The artificial graphite and its preparation method, negative electrode, and lithium-ion battery provided in the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application, and the descriptions of the embodiments above are only for the purpose of helping to understand this application. Furthermore, those skilled in the art will recognize that, based on the ideas of this application, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for producing artificial graphite, characterized by, The application relates to a preparation method of a biomass-based artificial graphite precursor. The raw coke powder is mixed with a modified solid-phase binder and a liquid-phase binder in a first mixing process and a second mixing process, granulation is performed, and a granulated precursor is obtained; wherein the modified solid-phase binder comprises a mixture of a solid-phase binder and fluorinated coke ultrafine powder; The granulated precursor is graphitized to obtain the artificial graphite.
2. The method for producing artificial graphite according to claim 1, characterized by, The solid-phase binder comprises one or more of coal tar pitch, petroleum pitch, phenolic resin, epoxy resin and polyacrylonitrile; and / or, The softening point of the solid-phase binder is above 150 DEG C; and / or, The liquid-phase binder comprises one or more of emulsified asphalt, liquid-phase asphalt, tar and polyacrylic acid.
3. The method for producing artificial graphite according to claim 2, characterized by, The liquid-phase binder further comprises a biomass-based binder, and the biomass-based binder comprises one or more of lignin, cellulose, protein, amino acid and starch; and / or, The mass percentage of the biomass-based binder in the liquid-phase binder is 20wt%-45wt%.
4. The method of claim 1, wherein the artificial graphite is prepared by the steps of: The mass ratio of the raw coke powder to the modified solid-phase binder is 100:(2-5); and / or, In the modified solid-phase binder, the mass ratio of the solid-phase binder to the fluorinated coke ultrafine powder is 100:(15-25); and / or, The mass ratio of the raw coke powder to the liquid-phase binder is 100:(6-8).
5. The method of claim 1, wherein the artificial graphite is prepared by the steps of: The preparation method of the fluorinated coke ultrafine powder comprises the following steps: The coke ultrafine powder is placed in a fluorine-containing atmosphere for fluorination treatment; the fluorine-containing atmosphere comprises fluorine-containing gas, and the fluorine-containing gas comprises one or more of fluorine gas, nitrogen trifluoride, sulfur hexafluoride, carbon tetrafluoride and hydrogen fluoride.
6. The method of claim 5, wherein the artificial graphite is prepared by a process comprising: The fluorination treatment comprises a first fluorination treatment and a second fluorination treatment in sequence; The first fluorination treatment comprises the following steps: the coke ultrafine powder is placed in a first fluorine-containing atmosphere, heated to 230 DEG C-270 DEG C, and kept for 1-2 hours; the first fluorine-containing atmosphere comprises fluorine-containing gas and protective gas, and the volume percentage of the fluorine-containing gas in the first fluorine-containing atmosphere is 10%-15%; The second fluorination treatment comprises the following steps: the coke ultrafine powder subjected to the first fluorination treatment is placed in a second fluorine-containing atmosphere, heated from 230 DEG C-270 DEG C to 330 DEG C-370 DEG C, and kept for 2-5 hours; the second fluorine-containing atmosphere comprises fluorine-containing gas and protective gas, and the volume percentage of the fluorine-containing gas in the second fluorine-containing atmosphere is 85%-90%.
7. The method of producing artificial graphite according to any one of claims 1 to 6, characterized by, Before the fluorination treatment, the coke ultrafine powder is subjected to nanocrystallization treatment; and / or, A liquid-phase dispersant is further added in the first mixing process; the mass ratio of the liquid-phase dispersant to the raw coke powder is (1-1.5):100; the liquid-phase dispersant comprises one or more of sodium carboxymethyl cellulose, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, fatty acid soap, sodium polyacrylate, polycarboxylate, hydroxyethyl cellulose and polyacrylic acid salt; and / or, The graphitization temperature is 2800 DEG C-3000 DEG C, and the graphitization time is 70-85 hours; and / or, The granulation comprises the following steps: the material obtained after mixing is heated to 250 DEG C-290 DEG C, kept for 4-6 hours, then heated to 630 DEG C-670 DEG C, and kept for 8-10 hours.
8. Artificial graphite, characterized by, The artificial graphite satisfies 0.89 < B < 1, B = 2T pressure under pore volume / pore volume under no pressure applied state.
9. A negative electrode characterized by comprising: The artificial graphite according to claim 8.
10. A lithium-ion battery, characterized by, The negative electrode according to claim 9.
Citation Information
Patent Citations
Surface purification of natural graphite and use of purified graphite in a carbon-lithium anode
CA2299626A1
Fine processing technology of heat conduction graphite flake gum for electronic equipment
CN106218193A
Superhard isostatic graphite and preparation method thereof
CN107522196A
Preparation method of special fine-particle graphite material
CN111170757A
Method for preparing artificial graphite by using tailing fine powder
CN116062744A